Complete chloroplast genome sequence of a vegetative Bermudagrass cultivar Tifeagle (Cynodon dactylon × Cynodon transvaalensis) (Bangladesh Journal of Botany, 2019)
Hybrid (Cynodonn dactylon × C. transvaalensis) is a widely distributed turfgrass and shows a great value of environment, horticulture and economic. Though, the chloroplast genome of C. dactylon has been reported, it might be helpful finding reasons that triploid bermudagrass shows a better drought and trampling tolerance than common bermudagrass through comparing chloroplast genome analysis. The present results showed the complete chloroplast genome of the C. dactylon × C. transvaalensis is 134655 bp in length. The tetramerous genome contained a large single copy (LSC) region (79,998 bp), a small single copy (SSC) region (12,517 bp), and a pair of inverted repeat (IR) regions (42,140 bp). In the chloroplast genome, 116 genes were predicted, including 83 protein-coding, 29 tRNA and 4 rRNA genes. Furthermore, a total of 80 repeat sequences were identified. Only 0.23% intergenicnon-collinear sequences were found between the chloroplast genome of Cynodon dactylon × C. transvaalensis and Cynodon dactylon.